FORMALISME PENDIDIKAN KARAKTER DI INDONESIA: Telaah Pendidikan Islam - Siti Patimah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
Character education in Indonesia still remains a very complex issue despite many efforts have been made by the government. The issue is still very evident in the behavior of the Indonesian nation which is still far from the ideal values of the character of the Indonesian nation itself. Therefore, in this paper the authors attempt to describe reality and the problem of educational character in Indonesia and in Islamic education point a view. This paper to present some of logical consequences of the concept of formalistic educational character in Indonesia that impact to Indonesian attitude which tending to have formal-religious in living on national activity.